Anticonvulsant and Neurotoxicity Evaluation of Some Novel Cyclohexyl-[4-substituted benzylidene/2-oxo-1,2-dihydro-indol-3-ylidene]thiosemicarbazides - Tripathi, Laxmi; Singh, Ranjit (Asian Journal of Chemistry, 2010)
A series of novel cyclohexyl-[4-substituted benzylidene/2-oxo-1,2-dihydro-indol-3-ylidene]- thiosemicarbazides were synthesized and screened for anticonvulsant activity in maximal electroshock induced seizure (MES) and subcutaneous metrazol (scMET) induced seizure models in mice. The neurotoxicity was assessed using the rotorod method. The compounds cyclohexyl- [4-(4-chlorophenoxy)-benzylidene]thiosemicarbazide (7d) and cyclohexyl-[2-oxo-1,2-dihydroindol- 3-ylidene]thiosemicarbazide (7i) emerged as the most promising one with anti-MES activity in mice i.p. All the compounds exhibited no neurotoxicity in rotorod method.